OPTIMISATION OF PROMOTIONS IN THE RETAIL INDUSTRY - Horden, Hendri; Bisset, Chanel (The South African Journal of Industrial Engineering, 2022)
Promotions are a powerful tool at retailers’ disposal, but they are often underutilised. This happens when retailers select a suboptimal mix and pricing of vendor items to place on promotion. In this study, a mathematical optimisation model is developed that specifies the optimal mix and pricing of vendor items to put on promotion. First, a solution approach is formed by reviewing existing solutions in the literature, followed by the formulation of a mixed-integer nonlinear programming model. This model is expressed as an integer linear programming model to simplify its solving capabilities. Second, the model is verified by applying it to a retail dataset to confirm that the model is correctly formulated and coded. Last, the model is validated to test its scalability and computational abilities. The results show that the model is highly scalable. This implies that retailers can implement the model practically and effectively to increase the profit obtained from promotion events.